Effects of Environmental Satisfaction on Family Displacement Case Study: Gohar Dasht Region, Karaj City - Ghasemi, Elnaz (Journal of Social Economics Research, 2017)
Residential Displacements from a place to another symbolize the urban viability. This mobility resulted in family movements can be rooted in various ways. Regarding to complexity of satisfactory rate, understanding of reasons are considered as difficult issues. In long term, The lack of appropriate attention to satisfaction rate of residents has led to negative impacts on Iranian city. Hence, effective indexes of residential mobility in this article are examined in a specific area named Karaj, Gohar Dasht. Analytical descriptive method was selected in conjunction with employing librarian research in assembling data. Moreover, 320 questioners with 30 indexes are used and analyzed. Obtained results denote the kind of possession, sense of belonging and income level as the most effective features on the sense of satisfaction and residential mobility.